2005
DOI: 10.1007/s11938-005-0007-y
|View full text |Cite
|
Sign up to set email alerts
|

Gastric and postpyloric total enteral nutrition

Abstract: The provision and maintenance of good nutrition in patients with acute and chronic illness is a fundamental part of standard medical and surgical care. Recently, there is great interest in using enteral nutritional support to reverse the morbidity and mortality associated with malnutrition. Enteral nutrition is preferred over parenteral nutrition because it is more physiologic, maintains intestinal structure and function, limits bacterial translocation, has less morbidity, has fewer complications, and is less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 48 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…Enteral nutrition, traditionally delivered directly into the stomach or postpylorus, is generally preferred over parenteral nutrition because it is more similar to natural physiological processes and reduces the incidence of complications, mortality, the cost, and the length of hospital stay. [1][2][3] Several randomized controlled trials have compared gastric and postpyloric feeding among patients with critical illnesses, but the results of these studies have been inconclusive and/or contradictory. 4 Neumann and DeLegge 5 have demonstrated that gastric tube feeding offers a safe and efficient means of enteral nutrition compared with small bowel feeding in a medical intensive care unit (ICU).…”
mentioning
confidence: 99%
“…Enteral nutrition, traditionally delivered directly into the stomach or postpylorus, is generally preferred over parenteral nutrition because it is more similar to natural physiological processes and reduces the incidence of complications, mortality, the cost, and the length of hospital stay. [1][2][3] Several randomized controlled trials have compared gastric and postpyloric feeding among patients with critical illnesses, but the results of these studies have been inconclusive and/or contradictory. 4 Neumann and DeLegge 5 have demonstrated that gastric tube feeding offers a safe and efficient means of enteral nutrition compared with small bowel feeding in a medical intensive care unit (ICU).…”
mentioning
confidence: 99%